SOME CLASSES OF STATISTICALLY CONVERGENT SEQUENCES OF FUZZY NUMBERS GENERATED BY A MODULUS FUNCTION - Cakan, U.; Altin, Y. (Univ Sistan & Baluchestan, 2015)
The purpose of this paper is to generalize the concepts of statistical convergence of sequences of fuzzy numbers defined by a modulus function using difference operator A and give some inclusion relations.
Keywords: Sequence of fuzzy numbers; Statistical convergence; Modulus function